Sturm-Liouville operator with general boundary conditions - Ciprian G. Gal (Electronic Journal of Differential Equations, 2005)
We classify the general linear boundary conditions involving $u''$, $u'$ and $u$ on the boundary ${a,b}$ so that a Sturm-Liouville operator on $[a,b]$ has a unique self-adjoint extension on a suitable Hilbert space.